Midwifery Care for Postpartum Mothers with Breast Milk Problems - Frida Indah Rahmaningrum; Ririn Indriani; Finta isti kundarti (KHD Production, 2025)
Failure of exclusive breastfeeding is caused by poor milk production, which can be influenced by stress, lack of understanding, and the mother's physiological condition. Inadequate milk production can negatively affect the growth and development of the baby. Non-pharmacological interventions such as oxytocin massage effectively stimulate oxytocin and prolactin hormones that play an important role in breast milk production. The purpose of this study was to provide postpartum midwifery care with the problem of breast milk not flowing through oxytocin massage therapy. This research used a case study approach to Mrs. FHP's complaint of breast milk not flowing in the right breast. Data were collected through interviews, observations, physical examinations, and documentation studies. The intervention was carried out by teaching the client's husband to use oxytocin massages, and monitoring was carried out for 7 days. Evaluation results showed increased breast milk production after oxytocin massage was performed twice a day for 15 minutes. Oxytocin massage is proven to be effective as a non-pharmacological intervention in overcoming the problem of poor milk production in postpartum women. Appropriate midwifery care can help mothers achieve exclusive breastfeeding success.